Volunteerism in a Disaster: A Real-Life Engagement Learning Experience - James Taylor; Jessica Averitt Taylor (The University of Alabama, 2022)
Like many of our neighbors, on April 27th of 2011 we sat in our living room watching on live television as menacing tornados destroyed several communities across Alabama. On that April night, the city of Gadsden appeared to have made it through the storm with minimal damage. Therefore, we spent the majority of our evening contacting our peers and colleagues who might have been initially impacted by the Tuscaloosa tornadoes. We spent the morning after the tornadoes discussing several approaches to usefully assist our community in assessing the relief needs in Tuscaloosa.